(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
جمعت عينات مياه شاطئية من ثلاثة مواقع على شاطئ مدينة جبلة وذلك خلال الفترة الممتدة من 30/10/2000 وحتى 2001/12/15 ، بالإضافة إلى ذلك تم جمع عينات من الأسماك المحلية خلال الفترة السابقة تتضمن الأنواع التالية: (بوري Chelon labrousus ، زليق Sparisoma sp.، منوري Oblada sp.، غريبة Siganus sp.، إسفنج Balistes sp.، نايلون Sargocentron sp. ، عروسة البحـر Coris julis) من شاطئ جبلة، وجرى استخلاصها ودراستها كيفياً وكمياً من اجل تعيين الفحوم الهيدروجينية الاليفاتية (AHCs) فيها باستخدام تقانة الكروموتوغرافيا الغازية GC-FID. سجلـت تراكيز الـ (AHCs) في المياه المدروسة في المجال 73.07-222.82 ng/l . كما تراوحت تراكيز الفحوم الهيدروجينية الأليفاتية في أنواع الأسماك المدروسة بين قيم دون عتبة الكشف (not detected) و 117.1 ng/g (dry wt. ) وقد سجلت أعلى التراكيز في أنسجة النوعين غريبة والبوري والتي بلغت 117.1 ng/g (dry wt. ) ، 101.77 ng/g (dry wt.)على الترتيب. Coastal waters have been collected from three sites of Jableh city during the period (30/10/2000-15/12/2001). Some local fish species have also been collected from Jableh coast during that period. They include: (Chelon Labrousus, Sparisoma sp., Olada sp., Siganus sp., Balistes sp., Sargocentron sp., Coris sp.). The samples have been extracted to determine the qualitative and quantitive content of Aliphatic Hydrocarbons (AHCs), using the GC-FID technique. The concentration of (AHCs) ranges between 73.07 and 222.82 ng/l. The concentration of (AHCs) in the studied fish species ranges between (not detected ) and (117.1 ng /g dry wt.); the highest concentration has been registered in tissues belonging to Chelon labrousus and Sigonus sp., notching(101.77 ng /g and 117.1 ng /g), respectively.